Nano-Theranostics for the Sensing, Imaging and Therapy of Prostate Cancers - Calatayud, David G.; Neophytou, Sotia; Nicodemou, Eleni; Giuffrida, S. Giuseppe; Ge, Haobo; Pascu, Sofia I. (Frontiers in Chemistry, 2022)
We highlight hereby recent developments in the emerging field of theranostics, which encompasses the combination of therapeutics and diagnostics in a single entity aimed for an early-stage diagnosis, image-guided therapy as well as evaluation of therapeutic outcomes of relevance cancer. Prostate cancer is one of the most common malignancies in men and a frequent cause of male cancer death. As such this overview is concerned with recent developments in imaging and sensing of relevance to prostate cancer diagnosis and therapeutic monitoring. A major advantage for the effective treatment of PCa is an early diagnosis that would provide information for an appropriate treatment. Various imaging techniques are being developed to diagnose and monitor different stages of cancer in general, and patient stratification is particularly relevant for PCa. Hybrid imaging techniques applicable for diagnosis combine complementary structural and morphological information to enhance resolution and sensitivity of imaging. The focus of this report is to sum up some of the most recent advances in the nanotechnological approaches to the sensing and treatment of prostate cancer (PCa). Countless reports have been published in physical sciences literature proposing methods to detect and treat PCa using nanoparticles (NPs), but the number of techniques approved for clinical use is relatively small. Targeted imaging using nanoparticles, radiotracers and biomarkers could result to a more specialised and personalised diagnosis and treatment of PCa. Another facet of this report is on reviewing aspects of the role of functional nanoparticles in multimodality imaging therapy considering recent developments in simultaneous PET-MRI (Positron Emission Tomography-Magnetic Resonance Imaging) coupled with optical imaging in vitro and in vivo, whilst highlighting feasible case studies that hold promise for the next generation of dual modality medical imaging of PCa.